Two Novel and Five Rare Mutations in the Non Coding Regions of the β-Globin Gene in the Iranian Population. (3rd July 2020) - Hamid, Mohammad; Zargan Nezhad, Ebtesam; Keikhaei, Bijan; Galehdari, Hamid; Saberi, Alihossein; Sedaghat, Alireza; Mohammadi-Anaei, Marziye; Shariati, Gholamreza
Abstract: β-Thalassemia (β-thal) is one of the most frequent genetic disorder in Iran with great mutational diversity. In this study, we describe two novel and five rare mutations in the non coding regions of the β-globin gene; these mutations were identified in the non coding regions of the β-globin gene ( HBB ) in the heterozygous state. Three alterations were detected in the promoter region, including −9 (C>G) [ HBB : c.59C>G (novel mutation)], −54 (G>A) ( HBB : c.-104G>A) and −57 (A>T) ( HBB : c.-107A>T), three changes in the 5' untranslated region (5'UTR) including +11 (C>G) [ HBB : c.-40C>G (novel mutation)], +41 (A>T) ( HBB : c.-10A>T) and +43 (C>G) ( HBB : c.-8C>G) and one mutation in the 3'UTR 62 (A>G) ( HBB : c.*62A>G). Five mutations including −54, −57, +41, +11 and +43 were predicted to be deleterious in all except one in silico prediction tool, and the remaining two mutations were found to be most likely polymorphisms. In conclusion, two novel mutations were reported for the first time worldwide and five rare changes have not been reported previously in any other part of Iran. In the absence of further data, it is not possible to consider them as mutations that determine an ascertained healthy carrier state.